The tempest - Dickins, Rosie; Unzner-Fischer, Christa Shakespeare, William (Usborne London, 2014)
Shakespeare's classic romantic comedy retold for children growing in reading confidence and ability. Prospero and his daughter Miranda are stranded on a desert island when a magical storm washes a royal ship ashore. Can Prospero conjure up a happy ending?